Aktuálne k problematike kvality a efektívnosti výkonu verejnej správy v SR - Beličková, Kornélia (Univerzita Pardubice, 2010)
The author´s paper has the aim to assess briefly the issue of quality and efficiency of the public administration in Slovakia today compared with the past, when the focus of attention in the state budget reporting was cash principle. Since has made some significant changes regarding the budgetary process as a whole, i.e. in all its phases (stages).
Keywords: state budget; budget process; changes in the budgetary process; government; budgeting information system